2008
DOI: 10.1080/00207540600818195
|View full text |Cite
|
Sign up to set email alerts
|

The relevance of outsourcing and leagile strategies in performance optimization of an integrated process planning and scheduling model

Abstract: Over the past few years the grown global competition has enforced the manufacturing industries to upgrade their old production strategies with the modern day approaches. As a result of which, recent interest has been developed towards finding an appropriate policy that could enable them to compete with others, and facilitate them to emerge as a market winner. Keeping in mind the abovementioned facts, in this paper the authors have proposed an integrated process planning and scheduling model inheriting the sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…In the literature, plethora of research has been conducted to address different issues related to outsourcing activity in manufacturing supply chain [18][19][20][21][22][23][24][25][26][27][28]. During the study, Zheng et al [29] found that information sharing is a critical issue for different segments of distributed manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, plethora of research has been conducted to address different issues related to outsourcing activity in manufacturing supply chain [18][19][20][21][22][23][24][25][26][27][28]. During the study, Zheng et al [29] found that information sharing is a critical issue for different segments of distributed manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…The outsourcing strategy effectively reduces makespan. Chan et al, (2009) extended their earlier work (Chan et al, 2006) and proposed an Enhanced Swift Converging Simulated Annealing (ESCSA) algorithm for scheduling. The proposed algorithm was compared with other optimisation methods such as GA, SA, TS and TS-SA algorithms and found that makespan came out 30 and 55 units for due date ≤ 45 and ≤ 75 respectively which outperformed comparatively.…”
Section: Other Approachesmentioning
confidence: 99%
“…Because outsourcing processes are not static and can be adapted according to the needs of the contracting company (Simmonds & Gibson 2008), in this context basing the outsourcing strategy on the experiences of professionals working in the logistics segment, and with knowledge in the operational routine, can be an opportunity for success (Mello et al, 2008). A successful relationship will also consider the external analysis of the LSP, based on the strategic positioning (Juga et al, 2008), because of the development of integrated planning to improve competitiveness (Chan et al, 2009), focused on creating competitive advantage (Kang et al, 2009).…”
Section: Analysis and Expected Benefitsmentioning
confidence: 99%
“…to reduce financial investment in activities and assets (Chan et al, 2009). In order to improve the efficiency of the resources, it is suggested to develop estimates for resource efficiency maximization (Chiang & Tzeng, 2009), based on the theory of transaction costs (Bandeira et al, 2010), before and after outsourcing (Lee et al, 2012), insofar as price is usually a preponderant factor for selection, at the expense of quality improvement (Anderson et al, 2011).…”
Section: /484mentioning
confidence: 99%